Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/gad.327163.119
|View full text |Cite
|
Sign up to set email alerts
|

Programming for T-lymphocyte fates: modularity and mechanisms

Abstract: T-cell development in mammals is a model for lineage choice and differentiation from multipotent stem cells. Although T-cell fate choice is promoted by signaling in the thymus through one dominant pathway, the Notch pathway, it entails a complex set of gene regulatory network and chromatin state changes even before the cells begin to express their signature feature, the clonal-specific T-cell receptors (TCRs) for antigen. This review distinguishes three developmental modules for T-cell development, which corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 168 publications
4
60
0
Order By: Relevance
“…This correlated with a block in T cell proliferation at the DN2-DN3 stage. DN2-DN3 stage of T cell development is associated with high levels of proliferation following TCRβ chain selection (52). A block in DN2-DN3 is likely caused by a block in proliferation which is consistent with the most downregulated pathways analyzed by RNA-seq being involved in DNA replication and cell proliferation ( Figure 3).…”
Section: The Adult Thymus Is Uniquely Affected By a Cns Tumorsupporting
confidence: 70%
See 4 more Smart Citations
“…This correlated with a block in T cell proliferation at the DN2-DN3 stage. DN2-DN3 stage of T cell development is associated with high levels of proliferation following TCRβ chain selection (52). A block in DN2-DN3 is likely caused by a block in proliferation which is consistent with the most downregulated pathways analyzed by RNA-seq being involved in DNA replication and cell proliferation ( Figure 3).…”
Section: The Adult Thymus Is Uniquely Affected By a Cns Tumorsupporting
confidence: 70%
“…We found that Rag1 and Rag2 genes, TCF3, TCF7, Gata3, and BCl11b, and Notch 1 were downregulated in thymi of GL261 tumor-bearing mice compared to controls ( Figure 3 D and S1 D). Downregulation of these genes can be consistent with a block between DN2-DN3 transition ( Figure 2 and (52,53,69,70)). Interestingly, another significantly downregulated gene in thymi of GL261-bearing mice compared to controls was Coro1a (Figure 3 Gene expression during experimental GBM induced thymic involution is not consistent with a stress response.…”
Section: Thymi Of Mice With Experimental Gbm Present With Unique Genesupporting
confidence: 54%
See 3 more Smart Citations